(untitled) (Hackensack, N.J., 2005)
orentz and CPT invariance is a feature of the Standard Model of particle physics and of theories of gravity such as Einstein's general relativity. However, an underlying theory such as strings may introduce small violations of Lorentz and CPT symmetry. This book consists of reviews from about 50 experts in the field, covering theoretical and experimental studies of these relativity-violating effects. It comprises the Proceedings of the Third Meeting on CPT and Lorentz Symmetry, held at Indiana University in Bloomington. The Meeting focused on recent developments involving fundamental spacetime symmetries and included theoretical scenarios and experimental searches for possible relativity violations. Experimental subjects covered include resonant-cavity and interferometric behavior of photons, oscillations of neutrinos and neutral mesons, clock-comparison measurements on the Earth and in space, astrophysical observations, tests with macroscopic matter, spectroscopy of hydrogen and antihydrogen, studies of particle properties and behavior, and gravitational tests. Theoretical topics covered include physical effects at the level of the Standard Model and beyond, the possible origins and mechanisms for Lorentz and CPT violations, and associated issues in particle physics, field theory, gravity, and string theory.
Keywords: CP violation (Nuclear physics),Lorentz groups